2020
DOI: 10.1002/pra2.213
|View full text |Cite
|
Sign up to set email alerts
|

Generating collective online information sharing: The framing effect of questions on response network

Abstract: Community Question‐Answering (CQA) sites are virtual communities where users participate in collective online information sharing. Questions in CQA sites serve as starting points for information sharing, eliciting a response network (RN), where nodes are the postings, while edges represent the responses between postings. This research employed framing theory to investigate how question frames affected their resulting RNs. Question frames were operationalized as conversational and informational. Social network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…In CQA, questions can be treated as goal-expressions for coordinating responses [27]. To explain the effect of goalexpressions on responses, framing theory posits that a goalframe selectively attracts responders' attention to a specific goal [17].…”
Section: Goal-frames In Questionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In CQA, questions can be treated as goal-expressions for coordinating responses [27]. To explain the effect of goalexpressions on responses, framing theory posits that a goalframe selectively attracts responders' attention to a specific goal [17].…”
Section: Goal-frames In Questionsmentioning
confidence: 99%
“…Community question-answering (CQA) has become a prevalent tool for information retrieval by exploiting "the wisdom of crowds" [20]. In particular, questions can be viewed as goalexpressions and potentially influence the responders [27]. Here, responders are answerers and commenters to the questions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rapid development of social question and answer (Q&A) communities empowers dispersed individuals to co‐create knowledge (Faraj et al, 2011; Zhang et al, 2019). As the starting point of knowledge co‐creation, user‐generated questions determine the scope of responses (i.e., answers and comments) (Wu et al, 2020a; Zhang et al, 2019). Earlier research has reported that questions spur knowledge exchange, initiate interactions, and encourage innovations (Bighash et al, 2018; Brooks & John, 2018; Wu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…To analyze question answerability, question cues are the linguistic characteristics for responders to identify the asker's needs (Banerjee, 2017; Chowdhury, 2003) and make decisions regarding whether to answer. Importantly, it was found that askers can utilize various question cues to specify goals (Wu et al, 2023): (1) cognitive cues include complexity and specificity that specify the cognitive goals for responders (Te'eni, 1990; Wu et al, 2022a); (2) emotional cues convey personal feelings (i.e., emotional expressiveness, self‐disclosure) (Fu et al, 2022; Kring et al, 1994; Shi et al, 2018); and (3) social cues refer to collaborative climate and politeness that stress on collective goals and support social interactions (Petrov et al, 2020; Wu et al, 2022b) (refer to Figure 1). However, the influences of question cues on responders' evaluations of question answerability are not yet well understood.…”
Section: Introductionmentioning
confidence: 99%